2017
DOI: 10.1007/s00726-017-2409-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of l-arginine/l-homoarginine/nitric oxide pathway for aortic distensibility and intima-media thickness in stroke patients

Abstract: Asymmetric dimethylarginine (ADMA) and L-homoarginine (hArg) are L-arginine (Arg) metabolites derived from different pathways. Protein arginine N-methyltransferase (PRMT) and subsequent proteolysis of proteins containing methylarginine residues release ADMA. Arginine:glycine amidinotransferase (AGAT) converts Arg to hArg and guanidinoacetate (GAA). While high concentrations of ADMA and low concentrations of hArg in the blood have been established as cardiovascular risk markers, the cardiovascular relevance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Recent studies have investigated cross-sectional associations between homoarginine concentrations and markers of vascular/metabolic homoeostasis and cardiac function. Haghikia et al 14 reported nonsignificant associations between plasma homoarginine concentrations and aortic distensibility and intima-media thickness in 78 patients with a recent cerebrovascular event. Pilz et al 15 observed significant inverse associations between serum homoarginine concentrations and N-terminal pro-B-type natriuretic peptide (P < .001) and midregional pro-adrenomedullin (P < .001), biomarkers of diastolic dysfunction and heart failure, in 1396 patients with preserved left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have investigated cross-sectional associations between homoarginine concentrations and markers of vascular/metabolic homoeostasis and cardiac function. Haghikia et al 14 reported nonsignificant associations between plasma homoarginine concentrations and aortic distensibility and intima-media thickness in 78 patients with a recent cerebrovascular event. Pilz et al 15 observed significant inverse associations between serum homoarginine concentrations and N-terminal pro-B-type natriuretic peptide (P < .001) and midregional pro-adrenomedullin (P < .001), biomarkers of diastolic dysfunction and heart failure, in 1396 patients with preserved left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 There is emerging evidence that homoarginine, a basic amino acid that is synthesized from L-arginine by the enzyme arginine:glycine amidinotransferase, exerts beneficial effects not only on endothelial function but also on markers of vascular homoeostasis and cardiac function. [14][15][16][17][18] Therefore, one can hypothesize that higher homoarginine concentrations might translate into better clinical outcomes in subjects with various degrees of cardiovascular risk. 12,13 Circulating homoarginine concentrations have shown inverse associations with surrogate markers of vascular and cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choe et al () reported that elevated l ‐homoarginine levels were associated with reduced all‐cause mortality in patients with ischemic stroke and that low l ‐homoarginine appears to be related to poor outcome after ischemic stroke. Moreover, l ‐homoarginine supplementation significantly improved cerebral damage and neurological deficits in mouse models with stroke (Haghikia et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of homoarginine are inversely correlated with the risk of cardiovascular disease and overall mortality (Marz et al ; Jud et al ), increased risk for fatal strokes (Haghikia et al ), congestive heart failure and left ventricular hypertrophy (Atzler et al , , Pilz et al ; Bahls et al ), aging (Marz et al ; Atzler et al ), smoking (Zwan et al ; Sobczak et al ; Atzler et al ; Vogl et al ), body mass index (Marz et al ; Atzler et al ; Pilz et al ), and pregnancy (Valtonen et al ). In addition, the effects of homoarginine on nitric oxide (NO) synthesis have been linked with increased risk of stroke and atherosclerosis as a reduction in homoarginine levels increased the aortic intima‐media thickness (Haghikia et al ). Low plasma homoarginine concentration is also significantly associated with the progression of chronic kidney disease (Drechsler et al ) and progression to dialysis and mortality (Ravani et al ), indicating that low plasma homoarginine concentrations might be an early indicator of kidney failure and a potential target for the prevention of disease progression.…”
Section: Introductionmentioning
confidence: 99%